CeO2 Nanorods and Nanocubes: Impact of Nanoparticle Shape on Dilatometry and Electrical Properties. Issue 7 (15th April 2016) - Knauth, Philippe; Harrington, George F.; Bishop, Sean R.; Saltsburg, Howard; Tuller, Harry L.
Abstract : The electrical and dilatometric properties of CeO2 nanopowders were examined as function of particle shape and size, including nanorods and nanocubes. Nanorods show continuous irreversible shrinkage, linked to particle reordering and compaction. Thermal expansion of CeO2 nanocubes was analyzed and was found to be consistent with literature data for microcrystalline ceria with no apparent nanosize effects. The electrical properties of the loosely compacted nanopowders were generally found to be characterized by n ‐type electronic conduction, except for proton conductivity contributions associated with adsorbed moisture at temperatures below 400°C. The P O2 and temperature dependences of the conductivity were examined in terms of defect chemical models. The lower effective enthalpy of reduction for nanorods (1.5 eV) in comparison with nanocubes (1.8 eV), both being much smaller than the value found for "bulk" ceria (4.7 eV), can be related to the larger surface to volume ratio of the nanorods, where oxide ion removal is more facile and less energy costly.